German Lessons and E-Mail Etiquette: Salutations and Greetings in Turkish University Student's Correspondence - Üstün, Ebru (Journal of Posthumanism, 2025)
The present study examines the impact of German language instruction on the email correspondence skills of Turkish university students, with a particular focus on the use of salutation and closing formulas in emails addressed to their instructors. To this end, students’ emails were analysed for their use of salutations and closing phrases, the types of these formulas, the influence of German language instruction on these aspects, and the preferred language for such correspondence. Frequency tables and the expanded classification system of salutations and closings in emails proposed by Al-Sayyed and Rabab’ah (2020), based on Bou-Franch (2011), were employed to analyse the data. The study sample consisted of students majoring in German as a Foreign Language at a Turkish university, who were still in their preparatory year. Data were collected and analysed from students across various levels of German instruction (A0, A1.1, A1.2, and A2.1). The results indicate a notable improvement in the use of salutations and closing phrases as students advanced in their German proficiency. At level A0, none of the participants used salutations or closings. However, a notable increase in the use of these formal elements was observed at higher levels, with students at A2.1 showing the highest adherence to formal email conventions.